Pneumatosis Intestinalis Associated with Juvenile Dermatomyositis - Takako Miyamae; Naoko Ishiguro; Maria Yonezawa; Katsutoshi Tokushige; Hisashi Yamanaka (Case Reports in Rheumatology)
We herein report a case of pneumatosis intestinalis (PI), a condition characterized by the presence of gas within the wall of the digestive tract, associated with juvenile dermatomyositis (JDM). A 16-year-old girl, diagnosed with JDM at the age of 10, presented with abdominal pain and distention. She developed PI based on radiological findings that also included a dilated large intestine, extraluminal gas, and secondary diaphragmatic elevation. She was observed with medical therapy including bowel rest and hyperbaric oxygen therapy. However, she ultimately developed a strangulated obstruction 5 years after presentation with PI and large intestine resection and colostomy were performed emergently.